Forest city: dream home or ghost town? - Goh, Gwyneth Xiao Hui (Nanyang Technological University, 2023)
Forest City is a residential development built in Iskandar Puteri, Johor, just off the West Coast of Singapore. Once promoted as a “living paradise” for Chinese residents to move into, the apartment complex seems to be the opposite of the Forest City dream. This photo essay examines where Forest City has been, where it is at now, and what the future might hold for the people living and working there.